The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5424/fs/2015243-07462
|View full text |Cite
|
Sign up to set email alerts
|

Geographic consistency in the seed dispersal patterns of Taxus baccata L. in the Iberian Peninsula

Abstract: <p><em>Aim of the study:</em> Seed dispersal is a crucial process in tree population dynamics. In the case of yew, <em>Taxus baccata</em> L., seeds are dispersed by birds and mammals in a non-random, microhabitat-dependent way, a pattern constraining population renewal and expansion. While skewed dispersal has been frequently found, we lack knowledge on how consistent are spatial restrictions across time and yew’s geographical range. This sort of information is required for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
1
8
0
Order By: Relevance
“…Fruits ripen asynchronously from late summer (August) to late autumn (November), but can remain on trees until late winter when not consumed by seed dispersers [ 19 ]. Yew relies essentially on avian frugivores for seed dispersal, especially on thrushes, Turdus spp., that feed on fruits directly from branches [ 19 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruits ripen asynchronously from late summer (August) to late autumn (November), but can remain on trees until late winter when not consumed by seed dispersers [ 19 ]. Yew relies essentially on avian frugivores for seed dispersal, especially on thrushes, Turdus spp., that feed on fruits directly from branches [ 19 , 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, we have accounted for this bias by counting some of the predated seeds found in situ as part of the seed rain. Although seed losses might have happened in the rock microhabitat, they were considered negligible (see also [ 34 , 38 , 39 ], for a validation of the methodology).…”
Section: Methodsmentioning
confidence: 99%
“…; McConkey et al . ; Hayes ; Lavabre & García ). Therefore, analysing the variation in species regeneration and the determinants of such variation at large scales is essential for more adequate management of species and habitats (García et al .…”
Section: Introductionmentioning
confidence: 99%
“…The fruits are eaten by several birds including winter flocking members of the thrush family as well as being hoarded and eaten by rodents [61]. However, Lavabre and García [62] did a study of the seed dispersal patterns of T. baccata across Spain and showed that the spatial distribution of the seeds in the landscape was heterogenous with the majority of the seeds consistently dispersed into forested microhabitats and almost none outside the forest. The results suggest that this generalized spatially restricted dispersal contributes to the lack of population range expansion.…”
Section: Species Delimitationmentioning
confidence: 99%